2005
DOI: 10.1080/08916930500050525
|View full text |Cite
|
Sign up to set email alerts
|

Atheroprotective immunization with MDA-modified apo B-100 peptide sequences is associated with activation of Th2 specific antibody expression

Abstract: Immunization with MDA apo B-100 fragments induce a shift from Th1 to a Th2 specific oxidized LDL antibody expression, but without a concomitant downregulation of plaque IFN-gamma expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 14 publications
2
57
0
1
Order By: Relevance
“…These results are in good agreement with our previous experimental studies demonstrating that immunization of apo E KO mice with MDA-p45 peptide results in an increase in specific IgG associated with a decrease in aortic plaque area and plaque content of inflammatory cells [15] . Moreover, treatment of apo E KO mice with human recombinant IgG specific for the MDA-p45 sequences also reduced aortic plaque area and decreased plaque inflammation [17].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are in good agreement with our previous experimental studies demonstrating that immunization of apo E KO mice with MDA-p45 peptide results in an increase in specific IgG associated with a decrease in aortic plaque area and plaque content of inflammatory cells [15] . Moreover, treatment of apo E KO mice with human recombinant IgG specific for the MDA-p45 sequences also reduced aortic plaque area and decreased plaque inflammation [17].…”
Section: Discussionsupporting
confidence: 82%
“…We have previously demonstrated that high IgM levels against a number of different aldehydemodified peptide sequences in apo B-100 are associated with increased severity of carotid disease and risk for development of acute myocardial infarction [13]. Immunization of apo E knockout (KO) mice with some of these native and aldehyde-modified apo B-100 peptide sequences induces an immunoglobulin switch from IgM to IgG that is accompanied by an inhibition of atherosclerosis [14][15][16]. To study the possible atheroprotective effects of this IgG we produced recombinant human IgG1 specific for a malondialdehyde (MDA)-modified peptide corresponding to the sequence between amino acids 661 and 680 in apo B-100 (p45) [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, atherosclerosis seems to be associated with production of autoantibodies recognizing Ags in the oxidized LDL particle (12,39,40). In contrast, an atheroprotective immunization of apo E-deficient mice with apo B-100 peptides resulted in increased levels of specific IgG Abs and a change in the immune response from IgG2a/c to IgG1 (14). Furthermore, clinical studies have revealed that high levels of IgG to native apo B-100 peptides are associated with lower risk of cardiovascular disease, whereas high Ab levels against the corresponding malondialdehyde-modified peptides are associated with more severe disease (12,19,41).…”
Section: Discussionmentioning
confidence: 99%
“…Immunization of apo E-deficient mice with some of these apo B-100 peptides induces an Ig switch from IgM to IgG that is accompanied by an inhibition of atherosclerosis (13)(14)(15). To study the possible atheoprotective effects of this IgG, we produced human IgG1 specific for an apo B-100 peptide.…”
mentioning
confidence: 99%